Oncogene OSTM1 Promotes Gastric-Cancer Metastasis by Modulating the Metastatic Microenvironment Through Altered Tumor-Cell Autocrine Signaling - Yucheng Tang; Yi Guo; Jiangyi Feng; Ziwei Wang (Current Issues in Molecular Biology)
Gastric cancer remains a malignancy with high incidence, mortality rates, and poor prognosis globally. Osteoclastogenesis-associated transmembrane protein 1 (OSTM1), a transmembrane protein overexpressed in various tumors, has unclear functions in gastric-cancer progression. This study explores OSTM1’s role in gastric-cancer proliferation and metastasis. OSTM1 expression was analyzed in gastric-cancer and adjacent tissues using immunohistochemistry and RT-qPCR. OSTM1 overexpression and knockdown cell lines were established to assess its effects on cancer-cell behavior through in vitro and in vivo experiments. Western blot and RT-qPCR were used to examine OSTM1’s regulation of S100A4 expression. OSTM1 was significantly overexpressed in gastric-cancer tissues, negatively correlating with TNM staging and overall survival. OSTM1 overexpression enhanced cancer-cell proliferation, colony formation, migration, and invasion, while its knockdown showed opposite effects. In vivo studies confirmed increased lung metastatic capability in high OSTM1-expressing cells. Mechanistically, OSTM1 positively regulated S100A4 expression, with S100A4 knockdown reducing OSTM1-enhanced metastasis. Gastric-cancer lung metastases showed higher microvascular density and α-SMA-positive fibroblast infiltration in the OSTM1 high-expression group. OSTM1 promotes gastric-cancer progression by upregulating S100A4 and modifying the tumor microenvironment through enhanced angiogenesis and fibroblast activation. OSTM1 represents a potential diagnostic and prognostic biomarker, with the OSTM1–S100A4 axis offering new therapeutic possibilities for gastric-cancer treatment.